THE CONTRACT OF EMPLOYMENT IN LABOUR LAW: OBSTACLE OR PANACEA? - Radley Henrico; Nicola Smit (Obiter, 2021)
The disparity of power in the employment relationship has courted argument that this imbalance continues to be perpetuated in the guise of “the contract of employment”, thereby rendering the contract of employment irrelevant and ineffective in advancing labour law rights. This article counters this view by illustrating the changed nature of the traditional foundation of the employment relationship, known as the contract of employment. The advent of a constitution and our courts’ willingness to develop and strengthen rights and obligations arising from the contract of employment are considered. In addition, the impact of legislation, collective bargaining and the recent more purposive interpretation of the statutory definition of “employee” are discussed. The writers conclude that, although the contract of employment is not a panacea to the  employment relationship, it is useful and expedient when interpreted and enforced against the backdrop of constitutional imperatives.